Choreographies of Contagion: Mapping Virality and Performative Identity on TikTok - Anies Fatmawati; Henrietta Noir; Shasa Indriyani; Jujuk Maryati; Fakhrul Setiobudi (Enigma in Cultural, 2025)
The rise of TikTok has inaugurated a new paradigm of digital culture centered on embodied participation. This study investigates viral dance challenges, proposing a novel framework—"choreographies of contagion"—to analyze them as structured, distributed performances that mediate identity. The framework moves beyond treating trends as mere content, instead examining the interplay between movement, affect, and algorithmic architecture. This study employed a six-month digital ethnographic approach, supplemented by a multi-modal analysis of a globally significant dance challenge (#WaveRider). A purposive sample of 500 videos and 20,000 associated comments were analyzed using a combination of kinesic analysis, to deconstruct the core movements, and reflexive thematic analysis, to map the patterns of creative deviation and affective response. The findings revealed a complex system of cultural production. A stable "kinesic blueprint" ensured replicability, acting as the trend's genetic code. This blueprint was then subjected to widespread "performative mutations," where users asserted agency and inscribed personal, cultural, and affective meaning onto the dance. These performances unfolded on an "algorithmic stage" that both disciplined and seduced users, shaping their actions. This process cultivated an "engineered communitas," a potent but transient sense of community forged through shared embodied practice and affective resonance. In conclusion, viral TikTok challenges are not spontaneous occurrences but sophisticated choreographic systems that harness the pleasure of mimesis and the desire for connection. The body on TikTok is a primary site for negotiating the tensions between individual agency and the logics of platform capitalism. This study concludes that virality is a deeply embodied, affective, and technologically mediated process, offering the "choreographies of contagion" framework as a critical tool for future scholarship.